Implementation of gabor filter and transform for image processing [electronic resource] - Rakesh Bharat Doshi, 1981-, author 607079; Yeak, Su Hoe, 1971-, supervisor 553892; Fakulti Sains 8004 (2016)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2016